Varying percentages of full uniform shading of a PV module in a controlled environment yields linear power reduction - Arthur James Swart; Pierre E Hertzog (Journal of Energy in Southern Africa, 2016)
Partial shading of a PV module has received much attention over the past few years, as it results in uneven cell power generation, compromising a PV system performance. Full uniform shading of a PV module has not received as much attention. This article correlates the percentage of full uniform shading of a given PV module within a controlled environment to its output power. The percentage of full uniform shading provided by shade nets was firstly determined. These shade nets are then used to cover a specific PV module (experimental system), while an identical PV module remains totally unshaded (control system). Increasing percentages of full uniform shading negatively affected the direct beam component in a linear way. Decreasing the light intensity falling on the PV model exhibited a linear increase in the percentage of output power reduction of the PV module. This is observed in that a shade net providing 36% of full uniform shading resulted in a 56% output power reduction, while a 63% full uniform shading net yielded 82% power reduction. These results hold a strong promise to improve current simulation modules that focus on determining the output power of a given PV array under specific environmental conditions or for specialised geographical locations.